Isolation and Identification of Pesticides Degrading Bacteria from Farmland Soil (Bangladesh Journal of Microbiology, 2019)
Pesticides are recognized to be the threat to the environment and associated with a wide range of serious diseases including respiratory diseases, cancer and even birth defects. In this study, six-different bacterial strains capable of degrading Carbofuran, Emamectin Benzoate and Thiamethoxam were isolated from eight different soil samples. The isolates were characterized by using different conventional and molecular methods. The strains were identified molecularly into different genotypes using amplified ribosomal DNA restriction analysis (ARDRA) and partial sequencing of 16S rDNA. The ARDRA pattern clustered them into 3 groups. Among the isolates three were identified as Achromobacter spp. and one as Diaphorobacter sp. by biochemical tests. It was further confirmed by the partial 16S rDNA sequencing. The two identified potential bacteria can be used for biodegradation of different pesticides which can have a significant environmental impact in soil farm.Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 90-94